THE IMPACT OF ISLAMIC BUSINESS ETHICS, ONLINE CUSTOMER REVIEWS, AND ONLINE CUSTOMER RATINGS ON DECISIONS TO PURCHASE HALAL COSMETIC PRODUCTS THROUGH SHOPEE - Inayah, Inayah; Adiba, Elfira Maya; Jessy, Rachela (Ekonomi Islam, 2024)
Purchasing transactions have grown rapidly due to the presence of the Internet. The use of Internet facilities allows business activities to be carried out anywhere and at any time without having to meet the parties in the transaction physically. Business activity using the Internet is called electronic commerce (e-commerce). Currently, in Indonesia, the online shop or online marketplace trend is on the rise. According to Research and Markets, a market research platform, the market in Indonesia is potentially growing by 19.0% throughout 2022. Some of the most popular online shops are Shopee, Tokopedia, Lazada, Zalora, and so on. The study aims to find out the influence of Islamic business ethics, online customer reviews, and online customer ratings on the decision to buy halal cosmetics products through Shopee among students of Trunojoyo Madura University. The study used quantitative methods and purposive sampling with respondents of as many as 100 students. The results of the study showed that Islamic business ethics (X1), online customer review (X2), and online customer rating (X3) have a significant influence on the purchase decision of halal cosmetic products. The combination of all variables studied influences each other in determining the decision of students to purchase illegal cosmetic products.